K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1: \(=6x^2+2x-15x-5-x^2+6x-9+4x^2+20x+25-27x^3-27x^2-9x-1\)

=-27x^3-18x^2+4x+10

2: =4x^2-1-6x^2-9x+4x+6-x^3+3x^2-3x+1+8x^3+36x^2+54x+27

=7x^3+37x^2+46x+33

5:

\(=25x^2-1-x^3-27-4x^2-16x-16-9x^2+24x-16+\left(2x-5\right)^3\)

\(=8x^3-60x^2+150-125+12x^2-x^3+8x-60\)

=7x^3-48x^2+8x-35

27 tháng 9 2024

         Bài 1:

\(\dfrac{11}{2}x\) + 1 = \(\dfrac{1}{3}x-\dfrac{1}{4}\)

\(\dfrac{11}{2}\)\(x\) - \(\dfrac{1}{3}\)\(x\) = - \(\dfrac{1}{4}\) - 1

-(\(\dfrac{33}{6}\) + \(\dfrac{2}{6}\))\(x\) = - \(\dfrac{5}{4}\)

\(\dfrac{35}{6}\)\(x\) = - \(\dfrac{5}{4}\)

  \(x=-\dfrac{5}{4}\) : (- \(\dfrac{35}{6}\))

 \(x\) = \(\dfrac{3}{14}\)

Vậy \(x=\dfrac{3}{14}\)

 

 

27 tháng 9 2024

Bài 2: 2\(x\) - \(\dfrac{2}{3}\) - 7\(x\) = \(\dfrac{3}{2}\) - 1

         2\(x\) - 7\(x\) = \(\dfrac{3}{2}\) - 1 + \(\dfrac{2}{3}\)

         - 5\(x\)    = \(\dfrac{9}{6}\) - \(\dfrac{6}{6}\) + \(\dfrac{4}{6}\) 

        - 5\(x\)    = \(\dfrac{7}{6}\)

           \(x\)    = \(\dfrac{7}{6}\) : (- 5) 

          \(x\)    = - \(\dfrac{7}{30}\)

Vậy \(x=-\dfrac{7}{30}\)

 

10 tháng 7 2021

Thế mày làm đi

 

10 tháng 7 2021

cho ít thôi thì làm

 

21 tháng 8 2018

\(A=\left(x+2\right)\left(x^2-2x+4\right)-\left(x^3-2\right)\)

\(\Rightarrow A=\left(x^3+8\right)-\left(x^3-2\right)\)

\(\Rightarrow A=x^3+8-x^3+2\)

\(\Rightarrow A=\left(x^3-x^3\right)+\left(8+2\right)\)

\(\Rightarrow A=10\)

21 tháng 8 2018

\(A=\left(x+2\right)\left(x^2-2x+4\right)-\left(x^3-2\right)\)

\(=x^3+8-x^3+2\)

\(=10\)

\(B=\left(x+2\right)\left(x-2\right)\left(x^2+2x+4\right)\left(x^2-2x+4\right)\)

\(=\left(x+2\right)\left(x^2-2x+4\right)\left(x-2\right)\left(x^2+2x+4\right)\)

\(=\left(x^3+8\right)\left(x^3-8\right)\)

\(=x^6-64\)

\(C=\left(x^2+3x+1\right)^2+\left(3x-1\right)^2-2\left(x^2+3x+1\right)\left(3x-1\right)\)

\(=\left(x^2+3x+1\right)^2-2\left(x^2+3x+1\right)\left(3x-1\right)+\left(3x-1\right)^2\)

\(=\left(x^2+3x+1-3x+1\right)^2\)

\(=\left(x^2+2\right)^2\)

\(D=\left(3x^3+3x+1\right)\left(3x^3-3x+1\right)-\left(3x^3+1\right)^2\)

\(=\left(3x^3+1+3x\right)\left(3x^3+1-3x\right)-\left(3x^3+1\right)^2\)

\(=\left(3x^3+1\right)^2-9x^2-\left(3x^3+1\right)^2\)

\(=-9x^2\)

\(E=\left(2x^2+2x+1\right)\left(2x^2-2x+1\right)-\left(2x^2+1\right)^2\)

\(=\left(2x^2+1+2x\right)\left(2x^2+1-2x\right)-\left(2x^2+1\right)^2\)

\(=\left(2x^2+1\right)^2-4x^2-\left(2x^2+1\right)^2\)

\(=-4x^2\)

7 tháng 10 2021

1) \(\Rightarrow16x^2+24x+9+9x^2-24x+16+4-25x^2=x\)

\(\Rightarrow x=29\)

2)

a) \(=x^2-9-x^2+6x-9=6x-18\)

b) \(=\left(3x-1+2x+1\right)^2=\left(5x\right)^2=25x^2\)

Bài 2: 

Ta có: \(P=3x\left(\dfrac{2}{3}x^2-3x^4\right)+9x^2\left(x^3-1\right)+x^2\left(-2x+9\right)-12\)

\(=2x^3-9x^5+9x^5-9x^2-2x^3+9x^2-12\)

=-12

Bài 1: 

a: Ta có: \(x\left(x^2+2\right)+2x\left(1-\dfrac{1}{2}x^2\right)=4\)

\(\Leftrightarrow x^3+2x+2x-x^3=4\)

hay x=1

b: Ta có: \(4x^2\left(x-1\right)+x\left(x^2+4x\right)=40\)

\(\Leftrightarrow4x^3-4x^2+x^3+4x^2=40\)

\(\Leftrightarrow5x^3=40\)

hay x=2

c: Ta có: \(3x\left(x-2\right)-3\left(x^2-3\right)=8\)

\(\Leftrightarrow3x^2-6x-3x^2+9=8\)

\(\Leftrightarrow-6x=-1\)

hay \(x=\dfrac{1}{6}\)

4 tháng 3 2020

a) (x - 2)3 + (3x - 1)(3x + 1) = (x + 1)3

<=> x3 - 6x2 + 12x - 8 + 9x2 - 1 - x3 - 3x2 - 3x - 1 = 0

<=> 9x - 10 = 0

<=> 9x = 10

<=> x = 10/9

Vậy S = {10/9}

b) (x + 1)(2x - 3) = (2x - 1)(x + 5)

<=> 2x2 - x - 3 - 2x2 - 9x + 5 = 0

<=> -10x + 2 = 0

<=> -10x = -2

<=> x = 1/5

Vậy S = {1/5}

c) (x - 1)3 - x(x + 1)2 = 5x(2 - x) - 11(x + 2)

<=> x3 - 3x2 + 3x - 1 - x3 - 2x2 - x = 10x - 5x2 - 11x - 22

<=> -5x2 + 2x + 5x2 + x + 22 - 1 = 0

<=> 3x = -21

<=> x = -7

Vậy S = {-7}

d) (x - 3)(x + 4) - 2(3x - 2) = (x - 4)2

<=> x2 + x - 12 - 6x + 4 - x2 + 8x - 16 = 0

<=> 3x - 24 = 0

<=> 3x = 24

<=> x = 8

Vậy S = {8}

e) x(x + 3)2 - 3x = (x + 2)3 + 1

<=> x3 + 6x2 + 9x - 3x = x3 + 6x2 + 12x + 8 + 1

<=> x3 + 6x2 + 6x - x3 - 6x2 - 12x = 9

<=> -6x = 9

<=> x = -3/2

Vậy S = {-3/2}

f) (x + 1)(x2 - x + 1) - 2x = x(x + 1)(x- 1)

<=> x3 + 1 - 2x = x3 - x

<=> x3 - 2x - x3 + x = -1

<=> -x = -1

<=> x = 1

Vậy S = {1}